2021
DOI: 10.35848/1882-0786/ac1d64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mg dopant in Al-composition-graded Al x Ga1−x N (0.45 ≤ x) on vertical electrical conductivity of ultrawide bandgap AlGaN p–n junction

Abstract: A vertical electrical conductivity of an ultrawide bandgap AlGaN p-n junction with Al-composition-graded Al x Ga 1−x N (0.45 ⩽ x) p-type layer was systematically investigated via experiments and numerical simulation. The experimental results revealed that the initial Al composition of the Alcomposition-graded AlGaN should be sufficiently high without Mg dopants to generate enough holes by polarization-induced doping even though the bandgap is higher than that of conventional bulk p-AlGaN. The mechanism behind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…16,17) Moreover, it was demonstrated that p-type conductivity can be achieved even without any impurity doping using this approach. [18][19][20] As a result, the low internal loss was achievable. 21) Although these technologies led to breakthroughs in the realization of AlGaN-based LDs in UVC regions during pulsed current operation, 22,23) the threshold current densities were still relatively high (10 kA cm −2 level) compared to blue laser diodes and continuous-wave (CW) lasing was not achieved.…”
mentioning
confidence: 99%
“…16,17) Moreover, it was demonstrated that p-type conductivity can be achieved even without any impurity doping using this approach. [18][19][20] As a result, the low internal loss was achievable. 21) Although these technologies led to breakthroughs in the realization of AlGaN-based LDs in UVC regions during pulsed current operation, 22,23) the threshold current densities were still relatively high (10 kA cm −2 level) compared to blue laser diodes and continuous-wave (CW) lasing was not achieved.…”
mentioning
confidence: 99%
“…Thus, alloy scattering remains the dominant scattering process limiting carrier mobility [ 19 , 55 , 57 ]. Recently, polarization doping was successfully used in the design of AlGaN UVB LEDs proving that the concept could be used in nitride optoelectronic devices [ 30 , 58 ]. The present work opens its application in InGaN systems for the design of long wavelength LEDs and LDs.…”
Section: Resultsmentioning
confidence: 99%
“…The problem of p-type doping is one of the roadblocks towards high power green UV lasers which have many promising applications. The best possible remedy is to use Mg and polarization doping simultaneously [ 30 ]. In this work, we will use the methods developed in [ 23 ] for the Ga-In-N system to obtain polarization-doping constants, verify the creation of mobile charge and its application to device design.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Mg doping into the polarization doped layer results in higher resistivity. 23) This is expected to be due to the introduction of donor defects associated with Mg doping; the decrease in efficiency and increase in voltage with increased Mg flow rate may be due to the degradation of the electrical properties of the polarization doped layer due to Mg diffusion into the polarization doped layer.…”
Section: Resultsmentioning
confidence: 99%